PENERAPAN PENDEKATAN MODEL-ELICITING ACTIVITIES TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP - Fadhiya Fadhiya; Ricky Yuliardi; Abdul Rosyid (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
Application of The Approach of Model-Eliciting Activities To Improved Mathematical Problem Solving Ability The Students SMP. The purpose of study is to improve the students mathematical problem solving by using Model-Eliciting Activities. the result of the initial test indicates that the average value of experimental class is 13,83 and the average value of control class is 16,01. Meanwhile the result of the final test shows that the average value 47of experimental class is 28,46 and theaverage value of control class is 25,08. Based on the outcome of the initial and final data analysis, it can be concluded that students mathematical problem solving by the learning Model-Eliciting Activities is better than konvensional learning. However, the increase of mathematical problem solving by the learning Model-Eliciting Activities is better than konvensional learning. Beside that, Model-Eliciting Activities showed a positive response from about half of students.